2014
DOI: 10.1371/journal.pone.0111420
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Resiliency Training Programs: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: ImportancePoor mental health places a burden on individuals and populations. Resilient persons are able to adapt to life’s challenges and maintain high quality of life and function. Finding effective strategies to bolster resilience in individuals and populations is of interest to many stakeholders.ObjectivesTo synthesize the evidence for resiliency training programs in improving mental health and capacity in 1) diverse adult populations and 2) persons with chronic diseases.Data SourcesElectronic databases, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(271 citation statements)
references
References 29 publications
13
240
0
18
Order By: Relevance
“…Specifically, the research was designed to assess for changes in self-reported mental health symptoms, resilience, mental health awareness, work engagement, and mental health stigma attitudes over a one-year time frame. We expected that, consistent with prior reports (Leppin et al, 2014;Robertson et al, 2015), there would be small to moderate improvements in mental health stigma attitudes immediately after R2MR training and that the improvements would be sustained at 6-and 12-month follow-ups. In addition, we expected small to moderate improvements across all factors (mental health symptoms, mental health knowledge, resilience, work engagement) at 6-and 12-month follow-ups after R2MR training.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Specifically, the research was designed to assess for changes in self-reported mental health symptoms, resilience, mental health awareness, work engagement, and mental health stigma attitudes over a one-year time frame. We expected that, consistent with prior reports (Leppin et al, 2014;Robertson et al, 2015), there would be small to moderate improvements in mental health stigma attitudes immediately after R2MR training and that the improvements would be sustained at 6-and 12-month follow-ups. In addition, we expected small to moderate improvements across all factors (mental health symptoms, mental health knowledge, resilience, work engagement) at 6-and 12-month follow-ups after R2MR training.…”
Section: Introductionsupporting
confidence: 57%
“…Resilience training programs are designed to sustain and protect employee well-being and performance in the face of adversity (Anderson, Vaughan, & Mills, 2017;Robertson, Cooper, Sarkar, & Curran, 2015). There have been two systematic reviews (Leppin et al, 2014;Robertson et al, 2015) evidencing the programs as having small to moderate effect sizes for improving resilience, mental health, and subjective well-being of participants (e.g. reductions in stress, symptoms of depression, negative affect).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that an intervention aimed at enhancing resilience levels has the potential to effectively reduce stress levels and increase students' general psychologic well-being. 41 There are limitations to this study. This study engaged the majority of the chiropractic student cohort and provided broad insights into this population.…”
Section: Discussionmentioning
confidence: 90%
“…To date there are a limited number of resilience-based intervention studies, particularly those conducted with diverse populations and in diverse settings. (Leppin et al, 2014) Poorer mental health among African American women may be mitigated by improving access to comprehensive, integrated and patient-centered quality health care. There should be better integration of screening to increase appropriate identification of mental illness, assessment, and support for African American women in a primary care clinic.…”
Section: Policy Implicationsmentioning
confidence: 99%